Cool-textured diets for use in baculovirus production. Issue 11 (2nd November 2017) - Zamora-Avilés, N.; Martínez, A.M.; Pineda, S.; Bravo-Patiño, A.; Figueroa, I.; Lasa, R.
ABSTRACT: The incorporation of baculovirus into semi-synthetic diets has been used for the inoculation of large batches of insect larvae reared under gregarious conditions. The preparation of most artificial diets involves heating to dissolve the agar gelling agent followed by cooling to ∼55–60°C whereupon virus occlusion bodies (OBs) are incorporated into the diet. To avoid exposure of thermolabile OBs to high temperatures, a cool-textured diet using soy fiber was evaluated as a simple method to inoculate batches of larvae with the baculovirus OBs. Spodoptera exigua larvae that fed on a diet with 120, 140 or 160 g/l of soy fiber, as a substitute for agar, had a similar weight gain over a 24 h period than larvae that consumed a standard agar diet. The larval weight gain with cool-textured diets with 140 g/l of soy fiber was not improved by the addition of chlorophyll, green food dye colour, or by the removal of ascorbic acid, sodium benzoate and potassium sorbate. Preliminary tests performed to determine the optimal OBs concentration needed for the inoculation of groups of four instar larvae in agar and soy fiber diets revealed no virus inactivation in heated diets with a similar optimal concentration of 36 OBs mg −1 for both diets. Moreover, no significant differences were observed in OB production when each type of diet was used to inoculate groups of 250 larvae reared gregariously in plastic containers. Cool-textured diets could be of interest for the production of baculoviruses that require a diet that can be prepared quickly and easily.